Catalonia a new history - Dowling, Andrew 1965- (Routledge, 2023)
Origins, from Pre-History to the Romans -- New Influences. Visigoths, Christianity and the Arabs, 400-800 -- Consolidation and expansion 800 to 1150 -- Aragon and the Mediterranean Empire 1150 to 1410 -- Decline and revolt 1415 to 1660 -- Political incorporation, economic advance 1660 to 1830 -- Social conflict, national revival and ideological dispute 1830-1939 -- Francoism and the democratic experience 1939-2008 -- Epilogue: The failed push for Catalan independence.
Serienzählung wurde doppelt vergeben
Includes bibliographical references and index
Erschien bereits im September 2022
Keywords: Geschichte 400-2008; Neuzeit; Mittelalter; Katalonien; Catalonia (Spain) / History